Protective effect of dimethyl fumarate for the development of pressure ulcers after cutaneous ischemia‐reperfusion injury. Issue 5 (12th May 2020) - Inoue, Yuta; Uchiyama, Akihiko; Sekiguchi, Akiko; Yamazaki, Sahori; Fujiwara, Chisako; Yokoyama, Yoko; Ogino, Sachiko; Torii, Ryoko; Hosoi, Mari; Akai, Ryoko; Iwawaki, Takao; Ishikawa, Osamu; et al.
Abstract: Ischemia‐reperfusion (I/R) is associated with various pathogenic conditions, and there has been increasing evidence that cutaneous I/R injury is associated with the pathogenesis of pressure ulcers (PUs), especially at the early stage presenting as non‐blanchable erythema. Several studies demonstrated that oxidative stress is a key player in I/R injury, and the inhibition of oxidative stress may be capable of protecting tissue damage after I/R injury in various organs including skin. Dimethyl fumarate (DMF) approved by the Food and Drug Administration is Nrf2 activator, and recent studies revealed the antioxidative and anti‐inflammatory effects of DMF on I/R injury in animal models. Our objective was to assess the effects of oral administration of DMF on the development of PUs after cutaneous I/R injury in mice. We found that DMF administration significantly decreased the size of PUs after cutaneous I/R. Cutaneous I/R‐induced oxidative stress was also significantly inhibited by DMF in OKD48 mice, in which oxidative stress can be visually assessed. In addition, DMF treatment decreased hypoxic area, the numbers of apoptotic cells, and vascular loss in I/R area. DMF treatment suppressed the infiltration of MPO + neutrophils and the production of proinflammatory cytokines in I/R site after cutaneous I/R injury. in vitro experiments, DMF treatment suppressed the production of reactive oxygen species in pericyte‐like cells. These results suggest that DMF treatment might prevent the formation of PUs induced by cutaneous I/R injury via suppressing oxidative stress and subsequent inflammation. DMF treatment during the early phase of decubitus ulcers might protect against further progression.